The percentage of contribution of some biomechanical indicators to the level of skillful performance of the high spiking of volleyball players - Fleah Rumeeh, Ammar (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to identify the value of some biomechanical indicators at the level of skill performance of high crushing hitting among volleyball players and the relationship between them , and the research problem was embodied in the absence of a study of the relationship of some biomechanical indicators to the level of skillful performance of high spiking in order to reach accurate performance artistic achievement that serve the sport and works to develop because it is linked to the conditions biomechanical right associated with the performance of the private , and the researcher adopted the descriptive approach, research sample included a 12 player They were tested on the level of skill of spiking high among volleyball players, center 4, and they were photographed using a type camera (CASIO). High-speed (120 r/w) search variables values were through imaging and the use of a program for the analysis of the motor (Kinovea 8.25). Was presented and analyzed and discussed results of the data and extract the value of the link variables more in line with the kinetic energy index corner of the trunk and high, were the most important research findings (that the increase in the kinetic energy of the efficiency of the body parts , whether linear or rotary, have a positive effect on the speed of the body starting and then achieve the completion of a distance better by keeping the amount of traffic law and highly effective influence on the technical performance of the research sample); it has recommended the researcher b (the importance of has evolved capacity Explosive and maximal On investment Properties Mechanical To body at the shape the performance Artwork Correct , and use kinematic analysis periodically during the identification of the mechanical changes that occur upon the rise of the players).